Respuesta :

Answer:

Option F

Step-by-step explanation:

F). x + y = 3 -------(1)

    x - 3y = -2 --------(2)

    Equation (1) minus equation (2)

    (x + y) - (x - 3y) = 3 - (-2)

    4y = 5

    y = 1.25

    Hence, y is positive.

G). x + y = 3 --------(1)

    x + y = -2 --------(2)

    Both the equations represent parallel lines.

    There are no solutions of the given equations.

H). x - 3y = -2 -------(1)

     x + y = -2 -------(2)

    Equation (2) minus equation (1)

    (x + y) - (x - 3y) = -2 - (-2)

     4y = 0

     y = 0

    Since, 0 is neither positive nor negative, y will be neither positive nor negative.

J). x + y = 3 -------(1)

    x - y = 3 --------(2)

    Equation (1) - Equation (2)

    (x + y) - (x - y) = 3 - 3

    2y = 0

    Hence, y is neither negative nor positive.  

    Therefore, Option F is the answer.